2021
DOI: 10.1016/j.omtm.2021.09.015
|View full text |Cite
|
Sign up to set email alerts
|

SAG therapy restores bone growth and reduces enchondroma incidence in a model of skeletal chondrodysplasias caused by Ihh deficiency

Abstract: Inactivation mutations in the Indian hedgehog (Ihh) gene in humans cause numerous skeletal chondrodysplasias, including acrocapitofemoral dysplasia, brachydactyly type A1, and human short stature. The lack of an appropriate human-relevant model to accurately represent these chondrodysplasias has hampered the identification of clinically effective treatments. Here, we established a mouse model of human skeletal dysplasia induced by Ihh gene mutations via ablation of Ihh in Aggrecan-positive (Acan+) cells using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 61 publications
(111 reference statements)
1
5
0
Order By: Relevance
“…Here we observed sparse but detectable ciliary anti-pSMO staining that was dramatically enhanced by treatment of embryos with SAG21k, demonstrating endogenous SMO phosphorylation in these structures and consistent with the ability of this SMO agonist to ectopically activate Hh signaling during embryogenesis (Fig. S10) [95][96][97][98][99] . Thus, SMO undergoes GRK2 phosphorylation during eye and brain development.…”
Section: Hh Signal Transduction In Vivosupporting
confidence: 84%
“…Here we observed sparse but detectable ciliary anti-pSMO staining that was dramatically enhanced by treatment of embryos with SAG21k, demonstrating endogenous SMO phosphorylation in these structures and consistent with the ability of this SMO agonist to ectopically activate Hh signaling during embryogenesis (Fig. S10) [95][96][97][98][99] . Thus, SMO undergoes GRK2 phosphorylation during eye and brain development.…”
Section: Hh Signal Transduction In Vivosupporting
confidence: 84%
“…Ho et al [ 30 ] reported that only 13.4% of cells are ciliated in enchondroma tissues, which significantly decreased compared with control articular cartilage ( Figure 1 ). Recently, we found that the cilium incidence and cilium length were comparable between human enchondroma cells and control articular chondrocytes, but the cilium orientation largely alters [ 31 ]. The different sample resources may contribute to variation in different samples, and the cilium features in more human enchondroma samples are needed to be identified in the future.…”
Section: Primary Cilia and Ciliary Proteins In Skeletal Diseasesmentioning
confidence: 99%
“…Hedgehog (Hh) concentration distribution gradient is essential for normal chondrocyte proliferation and differentiation. However, the Hh gradient is disrupted and showed a homogeneous pattern in enchondroma or osteochondroma [ 31 ]. Activated Hh signaling in the growth plate (Col2 α 1-Gli2 overexpressed mouse) leads to enchondroma in mice.…”
Section: Primary Cilia and Ciliary Proteins In Skeletal Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…The embedded samples were cryosectioned at 6 μm using a cryostat (CM1850, Leica). 52 Safranin O/fast green staining The mouse tibia was sectioned and stained with safranin O/fast green to visualize cartilage and assess the proteoglycan content, as described previously. 53 The samples on the slides were stained with Weigert's iron hematoxylin and fast green and then with 0.1% safranin O solution.…”
Section: Histologymentioning
confidence: 99%